Effect of ICS 205-930 (a specific 5-HT3 receptor antagonist) on gastric emptying of a solid meal in normal subjects. Issue 9 (September 1988) - Akkermans, L M; Vos, A; Hoekstra, A; Roelofs, J M; Horowitz, M
Abstract : The effects on gastric emptying of a solid meal of the specific 5-HT3-receptor antagonist ICS 205-930, 10 mg and 20 mg intravenously were assessed with a scintigraphic technique in 12 normals. The 50% emptying time was less, the lag phase was shorter and the post lag emptying rate was faster after 20 mg ICS 205-930 (p less than 0.02). After 10 mg ICS 205-930 the lag phase was significantly shorter compared with placebo (p less than 0.04). These results suggest that 5-HT3 receptors may be involved in the regulation of gastric emptying in man.